Bio-derived polymers for coating applications: comparing poly(limonene carbonate) and poly(cyclohexadiene carbonate). Issue 39 (20th September 2017) - Stößer, Tim; Li, Chunliang; Unruangsri, Junjuda; Saini, Prabhjot K.; Sablong, Rafaël J.; Meier, Michael A. R.; Williams, Charlotte K.; Koning, Cor
Abstract : Two fully bio-based polycarbonates, poly(limonene carbonate) and poly(cylcohexadiene carbonate), were post-functionalized via thiol–ene reactions and tested as future coating materials. Abstract : Two fully bio-based polycarbonates, poly(cyclohexadiene carbonate) (PCHDC) and poly(limonene carbonate) (PLC), are synthesised from carbon dioxide and cyclohexadiene oxide and limonene oxide. The low molecular weight polycarbonates are cross-linked by a photoinitiated reaction with trimethylolpropane tris(3-mercaptopropionate), via thiol–ene reactions. The cross-linking reactions are monitored using Raman spectroscopy and the reaction temperatures and times are optimised. Kinetic analyses of the cross-linking process suggest diffusion-controlled reactions for both polymers, despite the differences in the nature of alkene moieties (terminal vs . internal alkene). The resulting materials are evaluated for coating applications, they show promising solvent resistance and hardness and may be used in the future to prepare scratch-resistant coatings.